2017
DOI: 10.1186/s40529-017-0203-9
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco plants expressing the maize nitrate transporter ZmNrt2.1 exhibit altered responses of growth and gene expression to nitrate and calcium

Abstract: BackgroundNitrate uptake is a highly regulated process. Understanding the intricate interactions between nitrate availability and genetically-controlled nitrate acquisition and metabolism is essential for improving nitrogen use efficiency and increasing nitrate uptake capacity for plants grown in both nitrate-poor and nitrate-enriched environments. In this report, we introduced into tobacco (Nicotiana tabacum) the constitutively expressed maize high-affinity transporter ZmNrt2.1 gene that would bypass the tigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The nitrate transport capacity has been reported for the whole family of A. thaliana and O. sativa NRT2 proteins (Wei et al ., 2018; Wang et al ., 2018), as well as for the characterized NRT2 members of Brassica napus, Lycopersicon esculentum, Chrysanthemum morifolium, Cucumis sativa, Cassava and Brachypodium distachyon (Leblanc et al ., 2013; Fu et al ., 2015; Gu et al ., 2016; Li et al ., 2018; Wang et al ., 2019; L. Zou et al ., 2019). Furthermore, specific links between altered NRT2 gene expression obtained in mutant or overexpressing genetic backgrounds and nitrate‐related plant phenotypes havebeen reported in many plants, including Triticum aestivum and Zea mays (Fu et al ., 2015; He et al ., 2015; Taulemesse et al ., 2015; Gu et al ., 2016; Ibrahim et al ., 2017; Wei et al ., 2018; Li et al ., 2018; Wang et al ., 2018; Naz et al ., 2019; L. Zou et al ., 2019; Luo et al ., 2020). The reduced NO production and content detected in the Ljnrt2.4 nodules are consistent with a deficient support of the nitrate substrate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The nitrate transport capacity has been reported for the whole family of A. thaliana and O. sativa NRT2 proteins (Wei et al ., 2018; Wang et al ., 2018), as well as for the characterized NRT2 members of Brassica napus, Lycopersicon esculentum, Chrysanthemum morifolium, Cucumis sativa, Cassava and Brachypodium distachyon (Leblanc et al ., 2013; Fu et al ., 2015; Gu et al ., 2016; Li et al ., 2018; Wang et al ., 2019; L. Zou et al ., 2019). Furthermore, specific links between altered NRT2 gene expression obtained in mutant or overexpressing genetic backgrounds and nitrate‐related plant phenotypes havebeen reported in many plants, including Triticum aestivum and Zea mays (Fu et al ., 2015; He et al ., 2015; Taulemesse et al ., 2015; Gu et al ., 2016; Ibrahim et al ., 2017; Wei et al ., 2018; Li et al ., 2018; Wang et al ., 2018; Naz et al ., 2019; L. Zou et al ., 2019; Luo et al ., 2020). The reduced NO production and content detected in the Ljnrt2.4 nodules are consistent with a deficient support of the nitrate substrate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“… 16 ZmNRT2.1 exhibit altered responses of growth and gene expression to nitrate and calcium. 17 An oligomer composed by two ZmNRT2.1 and two ZmNRT3.1A might be involved in the NO 3 − uptake in maize roots upon induction. 18 In addition, transcriptional studies of maize treated with saline-alkali treatment revealed that NRT2.1 was significantly up-regulated.…”
Section: Introductionmentioning
confidence: 99%